Growth of tapered SiC nanowires on flexible carbon fabric : toward field emission applications - Wu, Renbing (2013)
Tapered silicon carbide (SiC) nanowires were directly grown on the surface of flexible carbon fabric by a chemical vapor deposition process. The products were systemically characterized by X-ray diffraction, field emission scanning electron microscopy, high-resolution transmission electron microscopy, selected area electronic diffraction, and energy-dispersive X-ray spectroscopy. The results revealed that the tapered nanowires were of single crystalline β-SiC phase with the growth direction along [111] and had a feature of zigzag faceting over the wire surfaces. Such faceting was created by a quasi-periodic placement of twinning boundaries along the wire axis, which can be explained by surface energy minimization during the growth process. Based on the characterizations and thermodynamics analysis, the Fe-assisted vapor–liquid–solid (VLS) growth mechanism of tapered SiC nanowires was discussed. Furthermore, field emission measurements showed a very low turn-on field at 1.2 V μm–1 and a high field-enhancement factor of 3368. This study shows that SiC nanowires on carbon fabric have potential applications in electronic devices and flat panel displays.